2007
DOI: 10.1016/j.febslet.2007.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism controls dimerization of the chloroplast FoF1 ATP synthase in Chlamydomonas reinhardtii

Abstract: Dimers and oligomers of F-type ATP synthases have been observed previously in mitochondria of various organisms and for the CF o F 1 ATP synthase of chloroplasts of Chlamydomonas reinhardtii. In contrast to mitochondria, however, dimers of chloroplast ATP synthases dissociate at elevated phosphate concentration. This suggests a regulation by cell physiological processes.Stable isotope labeling of living cells and blue-native PAGE have been employed to quantitate changes in the ratio of monomeric to dimeric CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, so far, no direct effect of phosphorylation on ATP synthase activity has been demonstrated in vivo. Furthermore, a metabolically controlled dimerization of the C. reinhardtii plastid ATP synthase has been shown (Schwassmann et al, 2007), but an effect on enzyme activity has not been demonstrated yet. Therefore, the reason for the discrepancy between the downregulation of the ATP synthase contents and the less pronounced reduction in activity currently cannot be fully resolved.…”
Section: Excess Atp Synthase Capacity In Wild-type Plantsmentioning
confidence: 99%
“…However, so far, no direct effect of phosphorylation on ATP synthase activity has been demonstrated in vivo. Furthermore, a metabolically controlled dimerization of the C. reinhardtii plastid ATP synthase has been shown (Schwassmann et al, 2007), but an effect on enzyme activity has not been demonstrated yet. Therefore, the reason for the discrepancy between the downregulation of the ATP synthase contents and the less pronounced reduction in activity currently cannot be fully resolved.…”
Section: Excess Atp Synthase Capacity In Wild-type Plantsmentioning
confidence: 99%
“…BN-PAGE with the Hoefer SE 600 system (18 3 16 3 0.15 cm 3 , 10 lanes) was performed as previously described (Schägger and von Jagow, 1991;Schwassmann et al, 2007); stacking gels with 3.5% acrylamide and separating gels with linear acrylamide gradients of 5 to 13% were used, and 250 mg solubilized protein was applied per lane.…”
Section: Bn-pagementioning
confidence: 99%
“…Furthermore, this kind of electrophoresis allows to enlighten the supramolecular organization of proteins (e.g. [2][3][4][5][6][7]) and even preparative applications are feasible [6,8]. Since the function of many enzymes depends on ATP, monitoring of ATP hydrolysis in native gels is an excellent tool to screen complex samples rapidly.…”
mentioning
confidence: 99%
“…1B, lane 3). Basing on preceding observations [2,3], the electrophoretic mobility is compared with a standard, i.e. the purified ATP synthase, to assign the bands.…”
mentioning
confidence: 99%
See 1 more Smart Citation